Payments Imbalances, Sudden Surges and Safeguards - TAN, Augustine H. H. (Institutional Knowledge at Singapore Management University, 1989)
The General Agreement on Tariffs and Trade (GATT) was founded on the key principles of nondiscrimination and transparency in the conduct of trade policy, with the tariff being the accepted instrument of protection. Today, there is a different global picture. US economic dominance has been severely eroded by the rise of Japan and the European Community. In addition to greater interdependence in trade, there is also greater capital-market integration. Also, the exchange rates of major countries are no longer fixed. These new developments have undermined some of the key foundations of the GATT, especially in: 1. the role of developing countries in the GATT, their special and differential treatment, and the question of reciprocity, 2. the balance of payments provisions, and 3. the ability of the GATT to contain protectionism. Several clauses in the GATT constitute exceptions to the most favored nation principle and provide safeguards.